Development of e-module assisted by hypertext preprocessor (PHP) to improve environmental knowledge of senior high school students - Qurniasty; Sueb; Rohman, Fatchur (AIP conference proceedings, 2023)
Pollution occurs due to a lack of environmental knowledge in the community, so it is important to provide a complex concept of environmental pollution, because students will later transfer their knowledge to their peers or to the community. Therefore education as a forum to provide education about the importance of environmental knowledge. In addition, learning in 2020 to 2021 uses online learning so that digital-based teaching materials are needed to make it easier for students. However, teaching materials on this subject are still scarce or still few. This study aims to produce an electronic module based on research on the diversity of macrozoobenthos based on project based learning (PjBL) assisted by a hypertext preprocessor (PHP) application to increase students' environmental knowledge. The electronic module development model used is the Lee and Owens development model which has stages, namely the stages of analysis, design, development, implementation, and evaluation. The data analysis technique used quantitative and qualitative percentage results. The test results on students obtained a percentage value of 86.14% with a very valid category. Therefore, the developed electronic module is valid and effective to improve environmental knowledge.